The Impact of Travel Experience on Tourist Satisfaction and Intention to Revisit towards Wellness Tourism in Thailand - Suntornteerasut, Punnapassorn; Darawong, Chonlatis; Wongvedvanij, Ramida (Journal of Business, Innovation and Sustainability (JBIS), 2024)
This study aims to examine the impact of travel experience on the satisfaction and intention to revisit of wellness tourism destinations in Thailand, considering various factors such as relaxation and relaxation, novelty, healthy food, physical environment, and service quality. Quantitative research method was conducted by collecting questionnaires from 261 foreign tourists, using descriptive analysis, and Structural Equation Modeling. The research found that the travel experience including resting and relaxation, novelty, healthy diet, physical environment, and service quality significantly affect satisfaction and intention to revisit. These research results can be applied to develop marketing strategies and service quality improvements to enhance tourist satisfaction and intention to revisit.